The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyg.2021.650736
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and Quality of Life of Families Participating in Two Different Early Intervention Models in the Same Context: A Mixed Methods Study

Abstract: Early intervention is developed following different types of service organization, which in turn require different professional and family roles. The aim of this study was to compare the perceived satisfaction and family quality of life amongst families receiving early intervention developed at centers in comparison to those receiving the routines-based early intervention in families’ homes, that is a family centered intervention in ecological environments. Under a transformative paradigm, a mixed methods desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In literature, recent studies showed how early interventions in natural environments, such as families' home, favour communication with families [55]. The RHF, despite the fact that it is a specialized structure, has characteristics in itself of a natural environment such as a home, allowing the families and their children with VI to be hosted inside it, with the opportunity for the families to share daily time and life experiences with other families, becoming this extra time an additional positive factor for supporting each other.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, recent studies showed how early interventions in natural environments, such as families' home, favour communication with families [55]. The RHF, despite the fact that it is a specialized structure, has characteristics in itself of a natural environment such as a home, allowing the families and their children with VI to be hosted inside it, with the opportunity for the families to share daily time and life experiences with other families, becoming this extra time an additional positive factor for supporting each other.…”
Section: Discussionmentioning
confidence: 99%
“…Improving family quality of life (QoF) (Giné et al, 2009;Gràcia et al, 2020;Verger et al, 2021) is defined as one of the central objectives of family-centered interventions. Family Quality of Life is a construct that recognizes the family's ability to self-perceive different subjective and objective aspects of their quality of life.…”
Section: Family Quality Of Life As Outcomes From Family-centered Prac...mentioning
confidence: 99%
“…The concept of family quality of life also refers to a shared sense of family well-being and is therefore composed of subjective indicators (Balcells-Balcells et al, 2011). The improvement of family quality of life (QoF) (Giné et al, 2010;García-Grau et al, 2018;Verger et al, 2021) is defined as one of the central objectives of family-centered interventions. Family quality of life is a construct that recognizes the family's capacity for self-perception of different subjective and objective aspects of their quality of life.…”
Section: Family Quality Of Life As Outcomes From Family-centered Prac...mentioning
confidence: 99%
“…Positive approaches to early intervention are built upon the understanding that infants and toddlers develop through trusting and caring relationships with adults (O'Connor et al, 2019;Stockall et al, 2012). As a result, the capabilities of adults who care for children who are at risk of developmental delays or have neurodevelopmental needs are built through the supports they are given (Beaumont et al, 2021;Verger et al, 2021) and these will be significant in supporting children's development and learning. There is ample evidence suggesting that the earlier supports are given the greater probability there is of an improved developmental trajectory for the child (Koegel et al, 2014).…”
Section: Benefits Of Early Interventionmentioning
confidence: 99%